2017
DOI: 10.1039/c7ta00481h
|View full text |Cite
|
Sign up to set email alerts
|

Highly anion conductive, alkyl-chain-grafted copolymers as anion exchange membranes for operable alkaline H2/O2 fuel cells

Abstract: Alkyl chain grafted AEMs have been demonstrated to be highly alkaline stable, anion conductive and fuel cell operable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…Recent studies have shown that cyclic ammonium (24)(25)(26)(27) and tetraalkyl ammonium cations, specifically those with long alkyl chains (18)(19)(20)(28)(29)(30), have better alkaline stability than traditional benzyltrimethyl ammonium cations (31)(32)(33). Other cations, such as imidazolium (16,21,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43), phosphonium (44)(45)(46)(47)(48)(49), and metal cations (50)(51)(52)(53)(54), have also been widely applied in various AAEMs.…”
Section: Significancementioning
confidence: 99%
“…Recent studies have shown that cyclic ammonium (24)(25)(26)(27) and tetraalkyl ammonium cations, specifically those with long alkyl chains (18)(19)(20)(28)(29)(30), have better alkaline stability than traditional benzyltrimethyl ammonium cations (31)(32)(33). Other cations, such as imidazolium (16,21,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43), phosphonium (44)(45)(46)(47)(48)(49), and metal cations (50)(51)(52)(53)(54), have also been widely applied in various AAEMs.…”
Section: Significancementioning
confidence: 99%
“…2,5,11 High stability and performance have been reported for a number of newly developed polymer groups, 1 such as, radiation graed ethylene tetrauoroethylene, 4 poly(aryl piperidinium) 12 and poly(phenylene oxide) (PPO). [13][14][15] This paper focuses on membranes with PPO as a backbone. This polymer family has been extensively studied for different side-chain congurations, and in some cases as co-polymers or as blend materials.…”
Section: Introductionmentioning
confidence: 99%
“…This polymer family has been extensively studied for different side-chain congurations, and in some cases as co-polymers or as blend materials. [13][14][15][16][17][18][19][20][21][22] All ex situ studies show high performances, such as conductivities of 20-90 mS cm À1 in contact with liquid water and stabilities of up to 200 h in aqueous 1 M KOH or NaOH at 80 C. 13,[16][17][18][19][20][21][22] However, poor stability with hydration cycling, and lowered conductivity for lower relative humidity have also been reported for these types of membranes. 16,23,24 In operating AEMFCs, single polarisation curves of PPO-based membranes have shown that these materials can be used in a fuel cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they generally suffer from low ion conductivity and poor chemical stability in strong basic conditions which profoundly affect the practical utilization [6,7]. Some strategies including new design of polymer architectures and cation chemistries, polymer modification of crosslinking, blend or composite, hybrid and so on have been attempted to solve these problems [8][9][10][11][12][13][14][15][16][17]. Encouraging results have achieved over the past decades, for example, the ion conductivity has been improved about one order of magnitude, from 0.001~0.01 S cm -1 to 0.01~0.1 S cm -1 [18].…”
Section: Introductionmentioning
confidence: 99%